2021
DOI: 10.3389/fnmol.2021.767965
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Aspects of the Neurodevelopmental Gene NR2F1: From Animal Models to Human Pathology

Abstract: The assembly and maturation of the mammalian brain result from an intricate cascade of highly coordinated developmental events, such as cell proliferation, migration, and differentiation. Any impairment of this delicate multi-factorial process can lead to complex neurodevelopmental diseases, sharing common pathogenic mechanisms and molecular pathways resulting in multiple clinical signs. A recently described monogenic neurodevelopmental syndrome named Bosch-Boonstra-Schaaf Optic Atrophy Syndrome (BBSOAS) is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 274 publications
(523 reference statements)
2
29
0
Order By: Relevance
“…Several lines of evidence argue against this assumption. (i) extensive phenotype analyses of Nr2f1 mutants from various laboratories have implicated this factor in control of cortical progenitor proliferation as well as cortical patterning, and laminar fate determination in postmitotic neurons (Tocco et al , 2021 ). Yet, a direct role for Nr2f1 in control of postmitotic neuron survival has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence argue against this assumption. (i) extensive phenotype analyses of Nr2f1 mutants from various laboratories have implicated this factor in control of cortical progenitor proliferation as well as cortical patterning, and laminar fate determination in postmitotic neurons (Tocco et al , 2021 ). Yet, a direct role for Nr2f1 in control of postmitotic neuron survival has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, POSTRE predicted a coding LOF mechanism, as the deletion eliminates one of the NR2F1 alleles. Both MEF2C and NR2F1 have been previously associated with neurodevelopmental deffects (Tocco et al, 2021; Zhang and Zhao, 2022). Therefore, the deletion could cause the loss of both NR2F1 and MEF2C function through distinct mechanisms, which in turn might define the phenotypic spectrum of this patient.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Nr2f1 binds to a promoter region closed to the transcription starting site (TSS) of the Mfn2 gene, which is associated to the H3K4me3 in the adult neural tissue ( Figure 4a ). We next crossed our Chip-seq dataset with previously published transcriptome data on the hippocampi of adult Nr2f1-heterozygous mice ( Nr2f1-het) (Chen et al , 2020), a validated BBSOAS mouse model (Bertacchi et al , 2019a; Jurkute et al , 2021; Tocco et al , 2021). By Gene Set Enrichment Analysis (GSEA), we found that among the 1053 enriched genes approximately 8% (82/1053) code for mitochondrial proteins, including the Mfn2 gene ( Figure 4b ).…”
Section: Resultsmentioning
confidence: 99%